An Exploratory Study of Beliefs Relating to The Covid-19 Health Protocols: Roles of Value and Demographic Factors - Widyarini , Nurlaela; Istiqomah, Istiqomah (International Conference on Sustainable Health Promotion, 2021)
The implementation of Covid-19 health protocol has become a collective movement. Although vaccination is still in progress, health protocols are still becoming the main strategy. This study aimed to discover the values and beliefs of the people in health protocols during the Covid-19 pandemic. There were 73 participants with an average age of 16.85 years old (SD=7.710), which were gathered conveniently. Most of them (69.9%) were female, and 46% of them were high school graduates. The Basic Value scale (Schwartz et al., 2012) with 52 items (=.940) was used to reveal the participants’ values and open-ended questions were used to explore beliefs relating to the Covid-19 health protocols. The result showed the values that the participants held were mostly maintenance of relationship by showing obedience, courtesy towards other people, honour, tolerance, and protection of the welfare of humans and nature. The female participants had higher average value conservation (mean=74.034; SD=8.71) than the male ones (mean=67.54; SD=10.58). There was a quite significant difference in value self-enhancement (F=2.711; p<.05) viewed based on education level. Education, sex, and age were good predictors in explaining the values of self-enhancement (F=3.631; p<.05), and openness to change (F=3.200; p<.05)